Thrombolysis with alteplase for acute ischaemic stroke in the Safe Implementation of Thrombolysis in Stroke-Monitoring Study (SITS-MOST): an observational study - Wahlgren, Nils; Hacke, Werner; Hennerici, Michael G. (The lancet, 2007)
BACKGROUND: The aim of the Safe Implementation of Thrombolysis in Stroke-Monitoring Study (SITS-MOST) was to assess the safety and efficacy of intravenous alteplase as thrombolytic therapy within the first 3 h of onset of acute ischaemic stroke. Under European Union regulations, SITS-MOST was required to assess the safety profile of alteplase in clinical practice by comparison with results in randomised controlled trials. - METHODS: 6483 patients were recruited from 285 centres (50% with little previous experience in stroke thrombolysis) in 14 countries between 2002 and 2006 for this prospective, open, monitored, observational study. Primary outcomes were symptomatic (a deterioration in National Institutes of Health stroke scale score of >or=4) intracerebral haemorrhage type 2 within 24 h and mortality at 3 months. We compared mortality, the proportion of patients with symptomatic intracerebral haemorrhage as per the Cochrane definition, and functional outcome at 3 months with relevant pooled results from randomised controlled trials. - FINDINGS: Baseline characteristics of patients in SITS-MOST were much the same as those in the pooled randomised controlled trials. At 24 h, the proportion of patients with symptomatic intracerebral haemorrhage (per the SITS-MOST protocol) was 1.7% (107/6444; 95% CI 1.4-2.0); at 7 days, the proportion with the same condition as per the Cochrane definition was 7.3% (468/6438; 6.7-7.9) compared with 8.6% (40/465; 6.3-11.6) in the pooled randomised controlled trials. The mortality rate at 3 months in SITS-MOST was 11.3% (701/6218; 10.5-12.1) compared with 17.3% (83/479; 14.1-21.1) in the pooled randomised controlled trials. - INTERPRETATION: These data confirm that intravenous alteplase is safe and effective in routine clinical use when used within 3 h of stroke onset, even by centres with little previous experience of thrombolytic therapy for acute stroke. The findings should encourage wider use of thrombolytic therapy for suitable patients treated in stroke centres.